2007
DOI: 10.1271/bbb.70168
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobiological Activity of Lignan: Effect of Benzylic Oxygen and Stereochemistry of 2,3-Dibenzyl-4-butanolide and 3,4-Dibenzyltetrahydrofuran Lignans on Activity

Abstract: The effect of oxidation degree at the benzylic position of 2,3-dibenzyl-4-butanolide and 3,4-dibenzyltetrahydrofuran lignans on the antimicrobiological activity was examined. The highest oxidation degree at the benzylic position of 2,3-dibenzyl-4-butanolide gave the greatest activity, and 3,4-dibenzoyltetrahydrofuran showed the highest antifungal activity. The relationship between stereochemistry and activity was also examined. Both enantiomers of cis-matairesinol were synthesized for the first time, one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 1 publication
0
21
2
Order By: Relevance
“…The antibacterial activity of the tetrahydropyran sesquineolignans, morinols A and B and their stereoisomers, was clarified for the first time. In our previous study, the tetra-substituted tetrahydrofuran lignan, 10) di-substituted tetrahydrofuran lignan, and di-substituted -butyrolactone lignan 11) showed antibacterial activity against gram-positive bacteria, but not against gram-negative bacteria. In this study of the tetrahydropyran sesquineolignan, the same result was apparent, showing activity against gram-positive bacteria.…”
Section: Antifungal Activity Of the Stereoisomers Of Morinols A And Bmentioning
confidence: 92%
See 2 more Smart Citations
“…The antibacterial activity of the tetrahydropyran sesquineolignans, morinols A and B and their stereoisomers, was clarified for the first time. In our previous study, the tetra-substituted tetrahydrofuran lignan, 10) di-substituted tetrahydrofuran lignan, and di-substituted -butyrolactone lignan 11) showed antibacterial activity against gram-positive bacteria, but not against gram-negative bacteria. In this study of the tetrahydropyran sesquineolignan, the same result was apparent, showing activity against gram-positive bacteria.…”
Section: Antifungal Activity Of the Stereoisomers Of Morinols A And Bmentioning
confidence: 92%
“…Since (À)-virgatusin, which is a tetra-substituted tetrahydrofuran lignan, and 3,4-dibenzoyltetrahydrofuran have respectively shown antifungal activity against Colletotrichum lagenarium and Bipolaris oryzae, 9,11) these fungal strains were included for this test. All stereoisomers showed antifungal activity against only Alternaria alternata at 0.5 mM.…”
Section: Antifungal Activity Of the Stereoisomers Of Morinols A And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…12) All stereoisomers and derivatives were prepared by the previously described method. [7][8][9][10] The enantiomeric excess of all stereoisomers of matairesinol prepared by the previous method was determined as more than 99%ee by using a chiral column. Assay of the IgM productive activity.…”
Section: Methodsmentioning
confidence: 99%
“…The stereoisomers of matairesinol and derivatives were synthesized by the previously described method. [7][8][9][10] Since IgE is an antibody for allergy, suppressing the activity of IgE-production would decrease the allergic symptoms, while promotive compounds would contribute to research into allergy. The IgM-and IgE-productive activities of secoisolariciresinol, which is a butanediol type of lignan contained in food plant, were examined in our previous study, and the IgM-accelerative production of (À)-and (þ)-secoisolariciresinol was observed; however, none of the stereoisomers of secoisolariciresinol affected the IgE-productive activity.…”
mentioning
confidence: 99%